IFN-γ transforms the transcriptomic landscape and triggers myeloid cell hyperresponsiveness to cause lethal lung injury - Verma, Atul K.; McKelvey, Michael; Uddin, Md Bashir; Palani, Sunil; Niu, Meng; Bauer, Christopher; Shao, Shengjun; Sun, Keer (Frontiers in Immunology, 2022)
Acute Respiratory Distress Syndrome (ARDS) is an inflammatory disease that is associated with high mortality but no specific treatment. Our understanding of initial events that trigger ARDS pathogenesis is limited. We have developed a mouse model of inflammatory lung injury by influenza and methicillin-resistant Staphylococcus aureus (MRSA) coinfection plus daily antibiotic therapy. Using this pneumonic ARDS model, here we show that IFN-γ receptor signaling drives inflammatory cytokine storm and lung tissue damage. By single-cell RNA sequencing (scRNA-seq) analysis, we demonstrate that IFN- signaling induces a paradigm shift in the transcriptome of airway immune cells, particularly by upregulating macrophage and monocyte expression of genes associated with inflammatory diseases. In the absence of IFN-, macrophage and monocyte TNF-α production is diminished in response to influenza and MRSA coinfection. Further evidence from conditional knockout mouse models reveals that IFN- receptor signaling in myeloid cells, particularly CD11c+ mononuclear phagocytes, directly promotes TNF-α hyperproduction and inflammatory lung damage. Collectively, the findings from this study, ranging from cell-intrinsic gene expression to overall disease outcome, demonstrate that influenza-induced IFN- triggers myeloid cell hyperresponsiveness to MRSA, thereby leading to excessive inflammatory response and lethal lung damage during coinfection.